(NkOMBINATORNYJ ANALIZ(B. (NzADA^I I UPRAVNENIQ (B:s (Nu^EBNOE POSOBIE (B/s - (NmENX[IKOW(B, (NmIHAIL wASILXEWI^s; (NrEWQKIN(B, (Na(B. (Nm(B.s; (NkOPYLOWA(B, (Na(B.(Nn(B.s; (NrYBNIKOW(B, (NkONSTANTIN aLEKSEEWI^s ((NmOSKWA (B:s (NnAUKA(B,s, 1982)
(NbIBLIOGR(B.: (NS(B. 359-360s
Keywords: (NmATEMATIKAs -- (NkOMBINATORIKAs